Detection of Newcastle Disease, Avian Influenza, dan Infectious Bronchitis Virus from Commercial with Respiratory Clinical Signs - Santoso, Ferdinand Prayogo Cahyo; Wahyuni, Agnesia Endang Tri Hastuti; Untari, Tri; Asmara, Widya; Wibowo, Michael Haryadi (Jurnal Sain Veteriner, 2025)
Clinical symptoms in the chicken’s respiratory system, such as sores, nasal discharge, gasping, and so on, can be caused by a variety of possible socks. These signs may be caused by a virus, usually followed by economic losses. Causative diagnosis, especially virus detection, is needed to establish the cause of the symptoms. The study aims to detect Newcastle Disease (ND), Avian Influenza (AI), and Infectious Bronchitis (IB) cases of respiratory symptoms in commercial chickens by 2023. The samples studied in this study were organs from commercial chicken broilers and layers with respiratory symptoms. The organ was prepared as a suspension, then centrifuged to take out the supernatants. Supernatants were extracted using commercial extraction kits to produce templates for molecular detection. Molecular detection was performed using the RT-PCR two-step method. Primer pairs were used for the detection of ND, AI subtypes H5 and H9, as well as IB. The results were visualized by electrophoresis with 1.5% agarose. Interpretation of the positive result of RT-PCR based on the appearance and length of amplicons compared with the positive control of each virus. Positive RT-PCR samples with thick amplicon quality were subjected to sequencing and bioinformatics analysis. Results of detection with RT-PCR against 41 samples are positive ND of 1 out of 8 samples (12.5%), AI of 2 out of 17 samples (11.7%), and IB of 5 out of 16 samples (31.3%). Based on the molecular detection with RT-PCR, the symptoms of respiration in commercial chickens are confirmed due to the cause, namely the virus: ND genotype VII-i, AI subtype H5 clade 2.3.2, AI subtype H9, and IB genotype GI-19 (QX-like).